Bolus in optimizing VMAT breast treatments. (September 2016) - Monti, A.F.; Brambilla, M.G.; Sarno, L.; Carbonini, C.; Ferrari, M.B.; Zanni, D.; Rottoli, F.; Arienti, V.; Torresin, A.; ,
Abstract : Introduction: Post mastectomy radiotherapy entails challenges in breast treatment due to thin targets next to lungs, heart, and controlateral breast. Photon fluence modulation can partially compensate the underdosage at the chest surface due to build up, but dose gradients are often generated inducing hot spots. Purpose: In this work we propose to associate VMAT treatment and chest bolus to homogenize PTV dose coverage. Materials and methods: Six patients underwent a CT scan with and without a 10 mm thick bolus. PTVs included the chest wall (PTVc) and regional lymph nodes (PTVn). A 6MV VMAT treatment was optimized for each patient with and without bolus using a TPS Monaco5.1 (Elekta). Plans were compared on the basis of PTVs coverage (V95%, D98% and D2%), dose homogeneity index (HI) and conformity index (CI); and dose to OARs, particularly to lungs, heart, contralateral breast and RVR. Results: When the bolus is removed, PTVc parameters significantly change. V95%, D98% and CI decrease respectively of 5.9, 4.1 and 11.5%, while D2% and HI increase respectively of 1.4 and 5.9%. No changes affected PTVn while all OARs doses are slightly lower without bolus (less than 1%). Acute skin toxicity was G1 in all patients. Conclusion: A bolus can improve the PTV coverage at the surface, reducing high dose regions without increasing skin toxicity. Being PTVn deeper into the patient, there are no differences between the two treatments. OARs received approximately the same dose with a not clinically significant small reduction in favour of the treatment without bolus. Disclosure: No relationships to disclosure.